The Level of Preschool Teachers’ Mastery of Metacognitive Thinking Skills: A Field Study on a Sample of Teachers in the City of M’sila - Benzetta, Baldia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aimed to precisely assess the extent to which kindergarten teachers in M'sila, Algeria, possess metacognitive thinking skills. Metacognition, often referred to as "thinking about thinking," represents a fundamental cognitive ability enabling individuals to monitor and regulate their own cognitive processes. This skill is paramount within educational settings for fostering effective and adaptive learning. The research focused on three core components of metacognitive skill: planning (the ability to devise strategies for learning and problem-solving), monitoring (the capacity to track and evaluate progress during a task), and evaluation (the ability to review outcomes and determine the effectiveness of strategies employed). The study was guided by clear and specific research questions designed to elucidate the following: What is the overall degree to which kindergarten teachers possess metacognitive thinking skills? Furthermore, what is their level of proficiency in each individual skill: planning, monitoring, and evaluation? These detailed questions facilitated a comprehensive analysis of the various facets of metacognitive thinking among the teachers. To achieve these objectives and address the formulated questions, the study employed a descriptive methodology. This approach allowed for the collection and analysis of data to accurately portray the phenomenon as it exists in reality. The primary data collection instrument was the Metacognitive Thinking Skills Scale, developed by Dr. Ali Fares in 2017. This scale is distinguished by its comprehensive coverage of the three dimensions of metacognitive thinking emphasized in the study (planning, monitoring, and evaluation), thereby ensuring the assessment's thoroughness and accuracy. The scale was administered to a sample of 40 kindergarten teachers actively involved in teaching at various kindergartens within M'sila. This sample was selected to represent the kindergarten teachers in the region, enhancing the generalizability of the findings to the broader population. Following data collection, statistical analysis was performed to determine the teachers' proficiency levels in the targeted skills. The results indicated the following: The overall possession of metacognitive thinking skills by kindergarten teachers was moderate. The possession of planning skills by kindergarten teachers was moderate. The possession of monitoring skills by kindergarten teachers was moderate. The possession of evaluation skills by kindergarten teachers was moderate.